Gender bias in the primary prevention of cardiovascular disease. (11th May 2022) - Kang, H; Tillmann, T; Morrison, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/introduction: Women receive less aggressive treatment for cardiovascular disease (CVD), partly due to a delayed or incorrect diagnosis. However, there is little research into whether this gender bias extends to primary prevention of CVD (i.e. prevention of CVD in those individuals with no prior CVD events), and the reasons behind this bias. Purpose: This study analysed gender differences in the primary prevention of CVD in the USA, using data from the National Health and Nutrition Examination Survey (NHANES) for the years 2015-2018. It also explored the drivers behind these differences. The hypothesis was that the known gender bias in CVD treatment also extends to primary prevention. Methods: The risk of developing CVD over the next ten years was calculated using the Pooled Cohort Equations (PCEs) for 9, 623 healthy men and women aged 40 to 79 years. 3, 035 participants were found to be at higher CVD risk (ASCVD score above 7.5%) and potentially eligible for statins. Individuals with prior diagnosis of CVD were excluded from this study. Multivariable logistic regression was used to calculate adjusted odds ratios (AOR) in the usage of preventive treatment between genders. Results: The results showed that men were 21% more likely to be prescribed statins than women whilst women were 20-37% more likely to be told to make behaviour modifications than men (Table 1). An interdisciplinary literature review showed that lower CVD risk perception in women is a likely driver of this gender difference. Conclusion: The well-known gender bias in the treatment of CVD also appears to take place in the primary prevention of CVD with statin therapy. These findings have highlighted the gender bias in primary prevention of CVD, supporting the scarce existing literature on this topic and providing more recent evidence in line with the updated CVD prevention guidance. This has implications in developing interventions based in the health system and community context to improve the treatment and survival outcomes for women with CVD.